Hachan Markas Lavrinovičius’ commitment to the Karaim language Trakai dialect preservation and revitalisation - Lavrinovič, Diana (Vilnius University Proceedings, 2024)
The paper introduces Markas Lavrinovičius’ most significant jobs in the Karaim cultural heritage preservation and revitalisation. Markas Lavrinovičius (1938–2011) was a Doctor of Science, Lithuanian Karaims’ Hachan, and the Chairman of the Lithuanian Karaims’ Religious Community. He was an active Karaim community member who made an important contribution to the language research and its revival. He described Karaim customs and traditions, compiled Karaim literary heritage, and prepared it for publication; he also described the Biblical stories in the Karaim language, translated relative Turkic-speaking nations’ folk fairy tales into Karaim, and compiled and computerised the Russian-Karaim dictionary. In addition, the article contains a review of the Karaim language coursebook titled 100 karaj tiliniń üriatiuviu. Troch karaj sioziu ([100 Karaim language lessons. Trakai dialect]) – one of his most significant works, containing a thorough research on the Karaim grammar, conducted by Markas Lavrinovičius and Diana Lavrinovič. Despite being surrounded by non-Turkic languages for 625 years, the Karaim language Trakai dialect has managed to preserve its purity and remain untouched throughout the centuries. Unfortunately, it currently faces the threat of extinction. Therefore, teaching the mother tongue was Markas Lavrinovičius’ ultimate goal.
Keywords: Karaims; Karaim language; Karaj; Trakai dialect; Turkic languages; Markas Lavrinovičius; Hachan; Cuman; Kipchak